Development of Laras Jiwa Gymnastics Model Using Traditional Music Of Central Java As An Effort To Improve The Cognitive Function Of The Elderly In The City Of Semarang - Silvia Indriyani Silvia Indriyani; ipang setiawan (Journal of Physical Education and Sports, 2026)
The increasing number of elderly people demands the formulation of innovative efforts to maintain the quality of life, especially in dealing with the decline in cognitive function that accompanies the aging process. This study aims to develop and evaluate the effectiveness of the exercise Laras Jiwa model based on traditional Central Javanese music in improving the cognitive function of the elderly. The research method used Research and Development (R&D) through ten stages of development. The study subjects were elderly aged 60–70 years from three clinics in Semarang City. The research instruments included validation sheets from health experts, gymnastics experts, art or music experts, observation sheets, and the Mini Mental State Examination (MMSE). The results of the Shapiro Wilk normality test showed that the pre-test and post-test cognitive function data were normally distributed (p > 0.05), so the analysis was continued using parametric statistics. The results of the paired sample t-test showed a significant difference between the MMSE scores before and after the implementation of the Exercise Laras Jiwa program for 12 weeks (p < 0.05). These findings confirm the effectiveness of  Exercise Laras Jiwa as a local culture-based physical activity model in improving the cognitive function of the elderly.